2010
DOI: 10.1203/pdr.0b013e3181ed8609
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gene Expression in the Ductus Arteriosus Are Related to Environmental and Genetic Risk Factors for Persistent Ductus Patency

Abstract: Three independent risk factors (immature gestation, absence of antenatal glucocorticoid exposure, and presence of the rs2817399(A) allele of the gene TFAP2B) are associated with patent ductus arteriosus (PDAs) that fail to close during prostaglandin inhibition. We hypothesized that these three factors may affect a common set of genes that increase the risk of persistent PDA after birth. We studied baboon ductus from term, preterm, and glucocorticoid-treated preterm fetuses and found that both immature gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…While changes in calcium entry and sensitization appear to account for the developmental increase in ductus tension with advancing gestation, the way this is accomplished seems to vary according to the species that is studied. For example, using quantitative PCR, we previously found that with advancing gestation RhoB expression is significantly increased in human (5) and mouse (unpublished results) ductussimilar to what Dr. Coceani's laboratory observed in fetal rats. However, in sheep (3,4)) and baboon (unpublished results) ductus there was no increase or decrease in RhoB expression.…”
supporting
confidence: 67%
“…While changes in calcium entry and sensitization appear to account for the developmental increase in ductus tension with advancing gestation, the way this is accomplished seems to vary according to the species that is studied. For example, using quantitative PCR, we previously found that with advancing gestation RhoB expression is significantly increased in human (5) and mouse (unpublished results) ductussimilar to what Dr. Coceani's laboratory observed in fetal rats. However, in sheep (3,4)) and baboon (unpublished results) ductus there was no increase or decrease in RhoB expression.…”
supporting
confidence: 67%
“…Other pathways implicated in ductal patency and closure in experimental models and humans include decreased expression/function of calcium and potassium channels, CD14+/CD163+ mononuclear cell adhesion to the ductal lumen (for neointimal growth), and isoprostane-mediated signaling via EP4 receptors. [20][21][22][23] Candidate gene studies have identified specific gene polymorphisms associated with PDA in human preterm infants, with polymorphisms in the TFAP2B and TNF receptor-associated factor 1 genes reported to be associated with the presence of a PDA. 20 Previously published reports have primarily focused on the platelet counts during the first few days of life.…”
Section: Discussionmentioning
confidence: 99%
“…These sick, preterm infants are the same babies that are likely to have delayed ductus closure after birth (24). We speculate that rather than contributing to PDA closure, platelet counts that remain in the highest quintile are merely an independent, surrogate marker of neonatal well being and of the presence of developmental factors that promote ductus closure after birth (25). …”
Section: Discussionmentioning
confidence: 99%